Adsorption Mechanism and Optical Behaviors of Typical Volatile Organic Compounds on Pristine and Cu/Ni‐Modified C3N Monolayer: A First‐Principles Study. Issue 1 (11th November 2022) - Ma, Kexin; Wang, Yanwen; Zheng, Yunxin; Xiao, Jianrong; Xu, Liang; Dai, Xueqiong; Wang, Zhiyong
Abstract: In this paper, the geometric and electronic structure of four gas molecules, including CH4, CH2 O, CH3 Cl and C6 H6, on pristine and Cu/Ni‐modified C3 N monolayer are investigated by using First principles. The calculations show that the Cu/Ni‐doping can effectively strengthen the gas adsorption ability of C3 N. Upon gas‐C3 N configuration, the adsorption energies are CH2 O (0.11 eV) > C6 H6 (0.09 eV) > CH3 Cl (0.08 eV) > CH4 (0.05 eV). For Cu‐C3 N configuration, the adsorption energies are C6 H6 (3.26 eV) > CH3 Cl (3.24 eV) > CH4 (3.22 eV) > CH2 O (3.13 eV). For Ni‐C3 N configuration, the adsorption energies are CH2 O (1.48 eV) > C6 H6 (0.66 eV) > CH3 Cl (0.39 eV) > CH4 (0.11 eV). It is worth mentioning that the magnetic moment is reduced to 0 µB when CH2 O are adsorbed on Cu/Ni‐C3 N, and the maximum charge transfer is 0.71 e, 0.62 e, respectively. Moreover, its optical properties of adsorption of Volatile organic compounds (VOCs) gas molecules are studied. It can be found that the two main absorption peaks locate at 3.0 × 10 5  cm −1  nm and 2.8 × 10 5  cm −1  nm at the range of ultraviolet and visible light. The calculated results provide the theoretical reference for Cu‐C3 N‐based VOCs sensors. Abstract : In this paper, the geometric and electronic structure of four gas molecules, including CH4, CH2 O, CH3 Cl, and C6 H6, on pristine and Cu/Ni‐modified C3 N monolayer are investigated by using first principles. It can be found that the Cu/Ni doping can effectively strengthen the gas adsorption ability of C3 N. The calculated results provide the theoretical reference for Cu‐C3 N‐based volatile organic compounds sensors.